2017
DOI: 10.1097/mcc.0000000000000420
|View full text |Cite
|
Sign up to set email alerts
|

Clinical examination for diagnosing circulatory shock

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 71 publications
0
34
0
Order By: Relevance
“…Clinical examination for diagnosing shock is fast, easy to conduct and low in cost, yet its diagnostic accuracy is questioned [3][4][5]. Particularly, physicians seem insufficiently capable of diagnosing a low cardiac index purely based on their clinical examination [6][7][8][9]. Previous studies scarcely specified their methods of clinical examination in terms of variables collected and definitions employed, leaving variability at the physician's discretion and making these studies difficult to reproduce [7,[9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical examination for diagnosing shock is fast, easy to conduct and low in cost, yet its diagnostic accuracy is questioned [3][4][5]. Particularly, physicians seem insufficiently capable of diagnosing a low cardiac index purely based on their clinical examination [6][7][8][9]. Previous studies scarcely specified their methods of clinical examination in terms of variables collected and definitions employed, leaving variability at the physician's discretion and making these studies difficult to reproduce [7,[9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the de nition of "delay" was depend on the length of exposure to severe sepsis in Han's study, while the actual onset time of severe sepsis is unknown truthfully, which might occurred outside the ICU, moreover, the etiologies for patients with unstable hemodynamics were not always explicit [23,24]. Although it's possible that patients would have received timely resuscitation regardless of the etiologies and whether the lactate level was measured or not, identifying patients could delay the lactate measurement and interventions.…”
Section: Discussionmentioning
confidence: 93%
“…mottled, cold and clammy vs. flushed skin, capillary refill) [1]. A systematic review [5] showed that estimation of the CO using three clinical signs including capillary refill time, mottling and skin temperature had a sensitivity of 12% and a specificity of 98%, suggesting a good performance to rule in the presence of low flow states [6]. The information from this clinical assessment often will guide the targeted expansion of the diagnostic workup.…”
Section: Clinical History and Physical Examinationmentioning
confidence: 99%